Legal Analysis of Offense: The Hate Speech of Religion And Denominations - Syah, Syawal Amirul; Said, Muhammad Fachri; Ramadhan, Muhammad Fauzi (Jurnal Hukum dan Keadilan, 2024)
The purposes of this research are 1) to know and analyze the law enforcement for hate speech against religions and denominations in Indonesia, 2) to know and analyze the factors which influence the law enforcement for hate speech against religions and denominations in Indonesia. The research used an empirical method that reviewed the processing and functioning of law in society, specifically analyzing the law enforcement for hate speech against religions and denominations in Makassar, Polrestabes, and Pengadilan Negeri Makassar. The result of this research shows that the law enforcement for hate speech against religions and denominations in Indonesia is still ineffective, with numerous instances of hate speech occurring without any affirmative action from law enforcement agencies. Additionally, the police have been unsuccessful in enforcing the law against hate speech, and there is a lack of regulations governing hate speech against religions and denominations. The society's black-and-white mindset, which separates religious affairs from state affairs, also contributes to this issue. The recommendations are, 1) the apparatus must have an active role to get through the spread of hate speech against religions and denominations, in particular under Circular No SE/ 06 / X /2015 about handling hate speech as a procedure, 2) construct particular rules about speech and preaching involving religion and denominations, 3) create particular rules for hate speech against religions and denominations to determine any hate speech that will be determined.